A New Methodology for Incorporating Chiral Linkers into Stapled Peptides - Serrano, Juan C. (Chembiochem, 2017)
Stapled peptides have arisen as a new class of chemical probe and potential therapeutic agents for modulating protein–protein interactions. Here, we report the first two‐component i,i+7 stapling methodology that makes use of two orthogonal, on‐resin stapling reactions to incorporate linkers bearing a chiral centre into a p53‐derived stapled peptide. Post‐stapling modifications to the chain were performed on‐resin and enabled rapid access to various peptide derivatives from a single staple. The stapled peptides have increased helicity, protease stability and in vitro binding affinities to MDM2 compared to the equivalent unstapled peptide. This approach can be used to generate a library of diverse stapled peptides with different properties starting from a single stapled peptide, with scope for much greater functional diversity than that provided by existing stapling methodologies.